Considering the extremely poor: Multidimensional poverty measurement for Germany - Daniel Nowak; Christoph Scheicher (University of Cologne, Institute of Econometrics and Statistics, 2014)
This paper applies the Alkire and Foster (2011) index of multidimensional poverty to German data. This is done with respect to the politically most important dimensions of poverty mentioned in the German federal government's report on poverty and wealth. Additionally, a modification of the identification step of the Alkire-Foster index is proposed to guarantee that individuals, who are extremely poor in only few dimensions, are not omitted by the index.
Keywords: I32; D63; 330; Poverty index; multivariate poverty; Alkire-Foster index; SOEP